PENGARUH EKSTRAK BUAH MENGKUDU (Morinda citrifolia L.) TERHADAP BILANGAN PEROKSIDA DAN KARAKTERISTIK SENSORI MINYAK BIJI KARET (Rubber Seed Oil) - Renadi, Raiyan; Ayu, Dewi Fortuna; Zalfiatri, Yelmira (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
Rubber seed oil are not currently used optimally, due to the high content of cyanide and free fatty acid. Cyanide can be derived by soaking process, and free fatty acid can be decreased by addition of noni extract.This research aims to study the effect of noni extracton the peroxide value and sensory characteristic of rubber seed oil. Research method used Completely Randomized Design which consists of 4 treatments and each treatment was repeated 4 times. Treatments of noni extract addition were 40%, 45%, 50%, and 55% of the total weight material. Data were statistically analyzed by using Analysis of Variance and continued with Duncan New Multiple Range Test at 5% level. Results of the analysis showed that the addition of noni extract was significantly effected on peroxide value, but not significantly effected on smell and colour of rubber seed oil. Based on this research, the best treatment was 45% noni extract addition which had average content of peroxide value 0,27meq/kg. Sensory assessment of rubber seed oil by panelist showed that the oil had a rancid smell and golden yellow colour. Keywords:Rubber seed oil, cyanide, free fatty acid, noni extract.